Molecular Detection of Helicobacter pylori ‎Infection in Gastric Biopsy Specimens by PCR (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Infection with Helicobacter pylori is associated with the development of different gastric disorders. Clinical outcome of H. pylori infection related to virulence factors that encoded by genes of this bacteria that can be used in a molecular detection such as the housekeeping genes; ureA and ureC. 16S rRNA is also used in bacterial diagnosis.Seventy-five patients with dyspeptic symptoms sent to esophago- gastroduodenal scope (OGD) unit at Merjan Hospital in Babylon Province.  They were diagnosed by specialist physicians and selected in the current study and were classified 43 patients had gastritis, 23 patients had peptic ulcer disease(PUD), 3 had growth like mass non cancer and 6 were normal as negative control.     The results of multiplex PCR and monoplex PCR revealed that a total of 49 (65.3%) cases were found positive for H. pylori by 16S rRNA and ureA, whereas ureC primer is less sensitive for bacterial detection